Legal harmonization as a key part of European integration of Ukraine - Чабах, Олександр Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
In this article are revealed some aspects of adaptation of the contemporary Ukrainian legislation and EU legislation as a necessary foreword of successful realization of European intentions of Ukraine. Ukrainian's European integration is a long term strategic goal.